Training in development and use of Growing Season Onset and Downscaled Seasonal Forecast Maprooms, Kigali, Rwanda, March 2017 - Corral, John del; Rose, Alison (2017)
In March 2017, a training was provided in Rwanda as part of the Rwanda Climate Services for Agriculture project, a U.S. Agency for International Development (USAID)-funded initiative that seeks to improve agricultural planning and food security management in the face of a variable and changing climate at both local and government levels. The project addresses both supply- and demand-side capacity regarding climate information. On the supply side, it is enhancing Rwanda Meteorology Agency (Meteo Rwanda)’s capacity to provide climate information tailored to agricultural needs by helping develop high-quality merged gridded historic datasets and an expanding suite of derived online products. Training participants included CIAT, the Ministry of Agriculture and Animal Resources (MINAGRI), the Rwanda Agricultural Board, and Meteo Rwanda on using downscaled seasonal forecasts. The training focused on using and understanding the new Historical Onset Date Maproom and the Seasonal Forecast Maproom.